Optimum Maturity and Quality Parameters in Grapes: A Review - Du Plessis, C.S. (South African Journal of Enology and Viticulture, 2017)
The quality of wine is without doubt largely dependent on the composition of the berries (Biol, 1977). In studies on grape quality, aspects of physiplogical, technological and industrial maturities have been covered by Kourakou (1974, 1977) and Marteau & Schaeffer (1978). These maturities refer to stages in the grape which are respectively, those where sugar production in the berry has generally ceased, where the grape has reached optimum quality and finally where grapes would give the most economical return. Burger (1977) pointed out the necessity for specifying parameters which could be used to classify grape quality. This also includes the aspect of grape maturity which is a most important facet of grape quality (Carrol el al., 1978) and regarded by some as being even more critical in this respect than viticultural practices (Slesinger, 1975).